In colon cancer cells fascin1 regulates adherens junction remodeling. Issue 3 (14th February 2023) - Esmaeilniakooshkghazi, Amin; Pham, Eric; George, Sudeep P.; Ahrorov, Afzal; Villagomez, Fabian R.; Byington, Michael; Mukhopadhyay, Srijita; Patnaik, Srinivas; Conrad, Jacinta C.; Naik, Monali; Ravi, Saathvika; Tebbutt, Niall; et al.
Abstract: Adherens junctions (AJs) are a defining feature of all epithelial cells. They regulate epithelial tissue architecture and integrity, and their dysregulation is a key step in tumor metastasis. AJ remodeling is crucial for cancer progression, and it plays a key role in tumor cell survival, growth, and dissemination. Few studies have examined AJ remodeling in cancer cells consequently, it remains poorly understood and unleveraged in the treatment of metastatic carcinomas. Fascin1 is an actin‐bundling protein that is absent from the normal epithelium but its expression in colon cancer is linked to metastasis and increased mortality. Here, we provide the molecular mechanism of AJ remodeling in colon cancer cells and identify for the first time, fascin1's function in AJ remodeling. We show that in colon cancer cells fascin1 remodels junctional actin and actomyosin contractility which makes AJs less stable but more dynamic. By remodeling AJs fascin1 drives mechanoactivation of WNT/β‐catenin signaling and generates "collective plasticity" which influences the behavior of cells during cell migration. The impact of mechanical inputs on WNT/β‐catenin activation in cancer cells remains poorly understood. Our findings highlight the role of AJ remodeling and mechanosensitive WNT/β‐catenin signaling in the growth and dissemination of colorectal carcinomas.